Influencing factors for strategic management development and its countermeasures in small and medium-sized enterprises in Guangdong Province of China / Li Ming - Li , Ming (2023)
Small and medium-sized enterprises (SMEs), known as "the most dynamic economic cells", are widespread and numerous throughout the world, and are small in scale but flexible in mechanism. After China's reform and opening up, SMEs have been growing rapidly, making them a key priority in the country's national economy and social development, and playing an important role in resource allocation, technology absorption and investment, opening up to the outside world, expanding foreign exchange earnings, activating markets, increasing employment and maintaining social stability. It is an essential and important part of China's economic development process and has an irreplaceable and special status for the development of China's economy. Therefore, in this era of challenges and opportunities, the study of the development of SMEs is an important element that deserves attention. This thesis firstly reviews and organizes the strategic management theory, the concepts related to SME development and the factors influencing SME development. A brief analysis of the current situation of SMEs in the Shenzhen region and the current strategic management situation is presented. Then, taking SMEs as the research object, a conceptual framework of the influencing factors on the development of SMEs is constructed on the basis of previous relevant studies, and a preliminary analysis of the influencing factors affecting the development strategies of SMEs is conducted from three aspects: internal SMEs, social relations and external environment respectively; then factor analysis is applied to extract the five public influencing factors affecting the development strategies of SMEs. The five public influencing factors affecting the development strategies of SMEs were extracted using factor analysis, namely, enterprise structure and strategic status, talent system, supply and marketing relationship, policy and legal environment, and financing environment, and using regression analysis, the business growth rate of the main business of SMEs was taken as the dependent variable, and regression analysis was conducted on the influencing factors of SMEs at various levels, to derive the influence of each public factor on the development strategies of SMEs. The thesis aims to use modern management tools and concepts to provide a better understanding of the development strategies of SMEs. The aim of this thesis is to make recommendations for the strategic development of SMEs using modern management tools and concepts. Therefore, after understanding what factors affect the development of SMEs, this thesis then further case studies the Balanced Scorecard, a strategic management tool that is highly utilized in the market. The thesis begins with a theoretical analysis, proposing general ideas and specific approaches to strategic management using the balanced scorecard, followed by a case study. The thesis proposes that the general idea of balanced scorecard strategy management is to establish a balanced scorecard strategy management system through strategy analysis and determination, strategy description, strategy shaping and resource allocation, strategy implementation and strategy feedback. The specific practices of Balanced Scorecard strategic management include: clarifying the strategic objectives, vision and mission of the company; launching publicity, education and communication; establishing a specific indicator system and criteria for the four dimensions; establishing a clear strategy map; data processing; indicator decomposition; formulating performance evaluation indicators and feedback and improvement, etc. Finally, based on the findings of the case study and empirical research, the advantages and disadvantages in the application of strategic management tools are pointed out, and corresponding countermeasures are suggested for the development strategies of SMEs from three aspects: internal, external and social relations, in the hope of providing a useful reference for enterprises in the process of implementing strategic management from strategy formulation to strategy implementation.